Student’s Affective Filter and Their Utilization of the English Language in the 21st-Century Classroom - Noah Mae Tadeo (Universitas Muria Kudus, 2026)
This study examined the correlation between students' affective filters and their use of English in the 21st-century classroom. Thus, a correlation analysis was used to examine whether there was a significant relationship among the following: learners' affective filter and their utilization of the English language; learners' profile and their affective filter; and learners' profile and their utilization of the English language. The respondents in this study were sampled using convenience sampling from Grade 7 to Grade 10 students enrolled at Wesleyan University-Philippines. The researchers used a questionnaire to assess respondents' socio-demographic profiles, affective filter, and English-language use. Based on the study's results, the respondents' demographic profile does not affect the learners' affective filter. On the other hand, most respondents' demographic profiles do not affect their use of English, except that gender affects their level of adaptability in using English. Lastly, it was also reported that the affective filter and language utilization in the 21st-century classroom have a significant relationship. Therefore, the study's results show that the affective filters among junior high school learners are correlated with their use of English. Hence, the researcher recommended that teachers help learners lower their filters by creating classroom environments that intentionally reduce them, such as maintaining a safe, collaborative, respectful, supportive, and in-depth classroom environment that makes students more comfortable participating.